PENGARUH KONSENTRASI MIMOSA TERHADAP SIFAT FISIK KULIT IKAN PARI TERSAMAK - Ruth Y. Situmorang; Latif Sahubawa; Siti Ari Budhiyanti (Universitas Gadjah Mada, 2008)
The physical quality of stingray leather is influenced by the types of tanning material (either natural or synthetic). Mimosa is a natural tanner produced of accacia skin extract. The objective of this research was to know the influence of mimosa concentration on the physical properties of tanned stingray leather. This experiment used Complete Randomized Design with four treatments of mimosa concentration, p1 (10%), p2 (12%), p3 (14%) and p4 (16%). The observed physical parameters were (a) tensile strength, (b) elongation at break, (c) rip strength and (d) organoleptic properties (flexibility and color). The data was analyzed with analysis of variance and Honesty Significant Different. Results indicated that the stingray leather treated with 14% mimosa gave the highest tensile strength (3383.11 N/cm2) and rip strength (429.40 N/cm2). The leather treated with 10 % mimosa resulted the highest elongation and 12% mimosa resulted the highest leather flexibility (2.53) and color (2.67). Though the HSD test did not show any significant differences between treatments, in general, the physical of tanned stingray leather of all treatment fulfilled the Indonesian National Standard of stingray leather (SNI.06-6121-1999). Therefore based on practical consideration, 10% mimosa was recommended for application.